"Play" in Gopas ritual in Kalinga province, Phiippines - Onoe, Tomoko (2011)
In the municipality of Pasil, Kalinga, Philippines, the practice of performing gopas rite persists to this day. A shaman, called manggogopas, conducts the ritual to give a person a guardian spirit. It consists of complicated processes with elements and activities that have symbolic meanings. However, in the last part of the ritual's climax, there is an annamed segment where the shaman and her assistant seem to relax, act irreverently, or play like children. While illustrating the gopas rite process, this article sheds light on how this ostensibly meaningless "play" portion paradoxically manifests significance as liminal space because it allows participants to obtain new understanding of their social order. This article points out that this part of the ritual highlights and differentiates both the symbolic and the substantial elements in the people's daily life.
Keywords: Shamanism; Shamanism -- Kalinga; Traditional medicine -- Pasil (Kalinga)